Perancangan Prototype Monitoring dan Akuisi Data Pengujian Noise Trafo Berbasis ESP32 - Fitri; Siradjuddin, Indrazno; Permatasari, Dinda Ayu; Wahono , Wahyu Tri; Albastomi, Abu Yazid (Politeknik Negeri Malang, 2024)
The noise level on the transformer is very important to be considered, because it can cause problems if it does not meet the standards. Excessive noise can violate regulations set by the Ministry of Environment regarding noise limit thresholds, In addition, excessive noise also indicates an indication of a bad transformer construction and will result in the performance of the transformer itself. PT Trafoindo Prima Perkasa, as one of the largest and first transformer manufacturers in Indonesia, tests every transformer produced, including its noise level, The testing is conducted in the Quality Check division. However, testing that is still done manually often causes queue buildup in the production line, along with the increasing demand, especially from PLN, a faster testing process is needed but still meets the set standards. Therefore, a faster, safer, and more efficient testing method is needed to support a continuous production. Based on this requirement, the author designs a prototype monitoring system and data acquisition of ESP32-based transformer noise testing to help speed up and simplify the testing process, so that the finished product can be sent immediately without reducing the quality and standards that have been set.